The Role of Polyphenols in Regulation of Heat Shock Proteins and Gut Microbiota in Weaning Stress. (7th September 2021) - Hussain, Tarique; Wang, Jing; Murtaza, Ghulam; Metwally, Elsayed; Yang, Huansheng; Kalhoro, Muhammad Saleem; Kalhoro, Dildar Hussain; Rahu, Baban Ali; Tan, Bie; Sahito, Raja Ghazanfar Ali; Chughtai, Muhammad Ismail; Yin, Yulong
Abstract : Gut microbiota is the natural residents of the intestinal ecosystem which display multiple functions that provide beneficial effects on host physiology. Disturbances in gut microbiota in weaning stress are regulated by the immune system and oxidative stress-related protein pathways. Weaning stress also alters gut microbiota response, limits digestibility, and influences animal productive performance through the production of inflammatory molecules. Heat shock proteins are the molecular chaperones that perform array functions from physiological to pathological point of view and remodeling cellular stress response. As it is involved in the defense mechanism, polyphenols ensure cellular tolerance against enormous stimuli. Polyphenols are nature-blessed compounds that show their existence in plenty of amounts. Due to their wider availability and popularity, they can exert strong immunomodulatory, antioxidative, and anti-inflammatory activities. Their promising health-promoting effects have been demonstrated in different cellular and animal studies. Dietary interventions with polyphenols may alter the gut microbiome response and attenuate the weaning stress related to inflammation. Further, polyphenols elicit health-favored effects through ameliorating inflammatory processes to improve digestibility and thereby exert a protective effect on animal production. Here, in this article, we will expand the role of dietary polyphenol intervention strategies in weaning stress which perturbs gut microbiota function and also paid emphasis to heat shock proteins in gut health. This review article gives new direction to the feed industry to formulate diet containing polyphenols which would have a significant impact on animal health.